A physical analysis of the condition of Malay manuscripts under the collection of The International Institute of Islamic Thought and Civilization (ISTAC) - Abdul Razak, Rajabi; Roslin Hazer, Nurul Amira; Othman, Raihan; Md. Zain, Dzul Haimi; Naamandadin, Nurul Akmam; Musa, Mukhtaruddin (UKM Press, 2021)
Manuscripts are synonyms for rare books, even though they are written by hand, beginning as early as the 13th century before the invention of printing technology. The Malay manuscript is a valuable national treasure filled with written and documented history of important events, the diversity of the natural sciences, religion, life and medicine. The valued treasures of knowledge and the secrets of life contained in this manuscript have contributed to the spread of Islam, human development, and modernization of technology as well as medicine. Therefore, it is important to preserve these manuscripts so that they remain intact and can be inherited by future generations. Thus, this research is intended to analyse the physical properties of the manuscript through a conservation perspective on Malay manuscripts from the 13th century to the early 19th century. A total of 30 copies from the collection of the International Institute of Islamic Thought and Civilization have been identified and analysed for their physical properties through visual methods and scientific analysis. Digital microscopes are one of the easiest tools which has been used to help identify the condition of the ink on the paper used. The type of paper was also identified by analysing the watermarks found on the manuscripts in the institute’s collection. The watermarks on the paper identified are as 3 stars in a shield (3 stars), lion, elephant, tre lune (3 crescent moon), man in a shield and fleur de lis. Apart from that, preliminary research also found that there are effects of damage on the structure, surface adhesion, chemical and biological damage that contribute to the factors of material weakness that result in the condition of the manuscript being fragile. Almost all manuscripts studied were handwritten using longer-lasting carbon ink. However, there are some manuscripts identified using ink from iron gall and, due to that, there are also burning effects found on the surface of the paper.